Finding Teo tula/talambuhay - Delos Reyes, Joselito D.; University of Santo Tomas Publishing House (Manila Inilathala at inilimbag ng University of Sto. Tomas Publishing House, 2018)
Biography of Teo T. Antonio, a Filipino poet, told in the form of poems.
Includes bibliographical references (pages 179-182).
In Tagalog.
Keywords: Antonio, Teo T; Philippine literature -- History and criticism; Poets, Filipino -- Biography